Metabolic and OXPHOS Activities Quantified by Temporal ex vivo Analysis Display Patient-Specific Metabolic Vulnerabilities in Human Breast Cancers - Koit, Andre; Timohhina, Natalja; Truu, Laura; Chekulayev, Vladimir; Gudlawar, Shivakumar; Shevchuk, Igor; Lepik, Katrin; Mallo, Lea; Kutner, Riina; Valvere, Vahur; Kaambre, Tuuli (Frontiers in Oncology, 2020)
Research on mitochondrial metabolism and respiration are rapidly developing areas, however, efficient and widely accepted methods for studying these in solid tumors are still missing. Here, we developed a new method without isotope tracing to quantitate time dependent mitochondrial citrate efflux in cell lines and human breast cancer samples. In addition, we studied ADP-activated respiration in both of the sample types using selective permeabilization and showed that metabolic activity and respiration are not equally linked. 3 times lower amount of mitochondria in scarcely respiring MDA-MB-231 cells convert pyruvate and glutamate into citrate efflux at 20% higher rate than highly respiring MCF-7 mitochondria do. Surprisingly, analysis of 59 human breast cancers revealed the opposite in clinical samples as aggressive breast cancer subtypes, in comparison to less aggressive subtypes, presented with both higher mitochondrial citrate efflux and higher respiration rate. Additionally, comparison of substrate preference (pyruvate or glutamate) for both mitochondrial citrate efflux and respiration in triple negative breast cancers revealed probable causes for high glutamine dependence in this subtype and reasons why some of these tumors are able to overcome glutaminase inhibition. Our research concludes that the two widely used breast cancer cell lines fail to replicate mitochondrial function as seen in respective human samples. And finally, the easy method described here, where time dependent small molecule metabolism and ADP-activated respiration in solid human cancers are analysed together, can increase success of translational research and ultimately benefit patients with cancer.